In search of a comprehensible set of endpoints for the routine monitoring of neurotoxicity in vertebrates: sensory perception and nerve transmission in zebrafish (Danio rerio) embryos - Stengel, Daniel; Wahby, Sarah; Braunbeck, Thomas (Environmental science and pollution research, 2017)
In order to develop a test battery based on a variety of neurological systems in fish, three sensory systems (vision, olfaction, and lateral line) as well as nerve transmission (acetylcholine esterase) were analyzed in zebrafish (Danio rerio) embryos with respect to their suitability as a model for the screening of neurotoxic trace substances in aquatic ecosystems. As a selection of known or putative neurotoxic compounds, amidotrizoic acid, caffeine, cypermethrin, dichlorvos, 2,4-dinitrotoluene, 2,4-dichlorophenol, 4-nonylphenol, perfluorooctanoic acid, and perfluorooctane sulfonic acid were tested in the fish embryo test (OECD test guideline 236) to determine EC10 values, which were then used as maximum test concentration in subsequent neurotoxicity tests. Whereas inhibition of acetylcholinesterase was investigated biochemically both in vivo and in vitro (ex vivo), the sensory organs were studied in vivo by means of fluorescence microscopy and histopathology in 72- or 96-h-old zebrafish embryos, which are not regarded as protected developmental stages in Europe and thus — at least de jure — represent alternative test methods. Various steps of optimization allowed this neurotoxicity battery to identify neurotoxic potentials for five out of the nine compounds: Cypermethrin and dichlorvos could be shown to specifically modulate acetylcholinesterase activity; dichlorvos, 2,4-dichlorophenol, 4-nonylphenol, and perfluorooctane sulfonic acid led to a degeneration of neuromasts, whereas both vision and olfaction proved quite resistant to concentrations ≤ EC10 of all of the model neurotoxicants tested. Comparison of neurotoxic effects on acetylcholinesterase activity following in vivo and in vitro (ex vivo) exposure to cypermethrin provided hints to a specific enzyme-modulating activity of pyrethroid compounds. Enhancement of the neuromast assay by applying a simultaneous double-staining procedure and implementing a 4-scale scoring system (Stengel et al. 2017) led to reduced variability of results and better statistical resolution and allowed to differentiate location-dependent effects in single neuromasts. Since acetylcholinesterase inhibition and neuromast degeneration can be analyzed in 72- and 96-h-old zebrafish embryos exposed to neurotoxicants according to the standard protocol of the fish embryo toxicity test (OECD TG 236), the fish embryo toxicity test can be enhanced to serve as a sensitive neurotoxicity screening test in non-protected stages of vertebrates.
Gesehen am 13.04.2018